Evidence for Dopamine Abnormalities Following Acute Methamphetamine Exposure Assessed by Neuromelanin-Sensitive Magnetic Resonance Imaging - Tang, Fei; Liu, Hui; Zhang, Xiao Jie; Zheng, Hui Hui; Dai, Yong Ming; Zheng, Li Yun; Yang, Wen Han; Du, Yan Yao; Liu, Jun (Frontiers in Aging Neuroscience, 2022)
Background Neuromelanin-sensitive magnetic resonance imaging (NM-MRI) is a newly developed MRI technique that provides a noninvasive way to indirectly measure of dopamine (DA) function. This study aimed to determine NM concentrations in brain regions following acute methamphetamine (MA) administration using NM-MRI and to explore whether NM-MRI can be used as a biomarker of DA function in nonneurodegenerative diseases. Methods Baseline NM-MRI, T1-weighted and T2-weighted images were acquired from 27 rats before drug/placebo injection. The control group (n=11) received acute placebo (Normal saline), while the experimental group (n=16) received acute MA. NM-MRI scans were performed 5, 30, 60 and 90 minutes after injection. Regions of interest (ROIs), including the caudate putamen (CP), nucleus accumbens (NAc), hippocampus (HIP), substantia nigra (SN) and crus cerebri (CC) were manually drawn. NM-MRI signal intensity in five brain regions at different time points were analyzed. Results In both the control and experimental groups, at each time point (baseline and 5, 30, 60, and 90 minutes), the SN exhibited significantly higher NM-MRI signal intensity than other brain regions (P<0.05). In addition, acute MA administration resulted in a continuous upward trend in NM-MRI signal intensity in each brain region over time. However, there was no such trend over time in the control group. The NM-MRI signal intensity of SN in the experimental group was significantly higher at the 60 and 90 minutes compared with that in the control group (P values were 0.042 and 0.042 respectively). Within experimental group, the NM-MRI signal intensity of SN was significantly higher at the 60 and 90 minutes compared with that before MA administration (P values were 0.023 and 0.011 respectively). Conclusions Our results indicated that NM was mainly deposited in the SN, and the conversion of DA to NM was most significant in the SN after acute MA exposure. Increased DA release induced by acute MA exposure may lead to increased accumulation of NM in multiple brain regions that can be revealed by NM-MRI. NM-MRI may serve as a powerful imaging tool that could have diverse research and clinical applications for detecting pathological changes in drug addiction and related non-neurodegenerative diseases.